Migration Law and the Externalization of Border Controls: European State Responsibility - Liguori, Anna (Routledge Research in EU Law, 2019)
Over the last few decades, both the European Union and European States have been implementing various strategies to externalize border controls with the declared intent of saving human lives and countering smuggling but with the actual end result of shifting borders, circumventing international obligations and ultimately preventing access to Europe. What has been principally deplored is the fact that externalizing border controls risks creating 'legal black holes'. Furthermore, what is particularly worrying in the current European debate is the intensification of this practice by multiple arrangements with unsafe third countries, exposing migrants and asylum seekers to serious human rights violations. This book explores whether European States can succeed in shifting their responsibility onto Third States in cases of human rights violations. Focusing, in particular, on the 2017 Italy-Libya Memorandum of Understanding, the book investigates the possible basis for triggering the responsibility of outsourcing States. The second part of the book examines how the Italy-Libya MoU is only a small part of a broader scenario, exploring EU policies of externalization. A brief overview of the recent decisions of the EU Court vis-à-vis two aspects of externalization (the EU-Turkey statement and the issue of humanitarian visas) will pave the way for the conclusions since, in the author's view, the current attitude of the Luxembourg Court confirms the importance of focusing on the responsibility of European States and the urgent need to investigate the possibility of bringing a claim against the outsourcing States before the Court of Strasbourg. Offering a new perspective on an extremely topical subject, this book will appeal to students, scholars and practitioners with an interest in European Law, International Law, Migration and Human Rights.